Giving Money to the Inca: Experiments and Theory on Social Norms and Tax Compliance in Peru - López Pérez, Raúl (2019)
We report data from an experiment in Peru where subjects anonymously decide how much of their endowment they donate to the Peruvian government. The standard rational choice model and several well-known models of non-selfish preferences predict zero giving. Yet we observe that around 75% of the subjects give something (N = 164), with substantial heterogeneity. Further, individual donations depend negatively on (a) beliefs about corruption in Peru and positively on (b) level of support of the actual government and (c) beliefs about the average donation by other subjects. Our data is consistent with a theory based on consequentialist norms, which we develop in detail. This paper contributes to a recent literature on tax morale emphasizing the importance of non-standard motivations on tax compliance, and suggests that taxpayers are willing to give money to the government (e.g., paying taxes) if they believe that enough others give as well and that taxes are not wasted or ‘stolen’ by the government, but used to promote social welfare.